PELO SAGRADO DIREITO DE DECIDIR: A CONTRIBUIÇÃO DE CATÓLICAS PELO DIREITO DE DECIDIR NAS DISCUSSÕES SOBRE LAICIDADE, DIREITOS REPRODUTIVOS E DESCRIMINALIZAÇÃO DO ABORTO NO BRASIL. - Campanaro, Priscila Kikuchi (2014)
This thesis aims to present an analysis of the relationship between religion and politics from a gender perspective, aiming to show how the relationship between church and state legitimizes sexual inequalities present in Brazilian society. This analysis seeks to highlight how political practices of the country have undermined the possibility of expansion of reproductive rights due to historical influence of the Catholic worldview regarding sexual morality. This religious influence, as regards the extension of public policies for reproduction, adversely affects the lives of women, particularly poor women and hurts the secular character of the Brazilian State. In this sense , the dissertation also highlights the situation is looking features the work of Catholics for a Free Choice, a possibility of political action and theoretical contribution, which is against the radical discourse on abortion arising from the hierarchy of the Catholic Church and is shared by fundamentalist sectors of other Christian denominations. Catholics for a Free Choice aims to build a feminist ethical-theological discourse to support the decriminalization of abortion and the right of women to decide about their reproductive lives without suffering any hindrance or discrimination for their decisions.